Pengaruh Variasi Arus terhadap Kekuatan Bending pada Pengelasan Plat A36 Menggunakan Las SMAW (Shielded Metal Arc Welding) - Chandra, Shandika; Waskito, Waskito; Jasman, Jasman; Putra, Randi Purnama (MASALIQ, 2023)
The use of A36 plate in the construction sector is closely related to connecting or welding between metals because it is useful in assembling a product to lighten human work. Examples of the use of A36 plate in the construction sector can be seen in trellis workshops, where this plate is often used as a support or support in making a balcony or canopy. However, sometimes workers do not understand how strong the plate is after being treated with welding, often they just guess at the durability of the plate, so this can cause various kinds of losses. Starting from damage to work objects to causing work accidents that result in loss of life. Therefore, this research examines the effect of variations in current strength on bending strength. This test was carried out on A36 plate material which was subjected to welding effects with varying currents of 80A, 100A, 120A and 140A. and a bending test was carried out using the ASTM E190-14 test standard, the results of this test were that at a current of 80A the bending strength value was 161.173 N/〖mm〗^2. Current 100A with a value of 229.851 N/〖mm〗^2. Current 120A with a value of 270.374 N/〖mm〗^2. And a current of 140A with a value of 374.839 N/〖mm〗^2. The test object with a current strength of 140A is the test object that has the highest bending strength value.